Crepes and galettes from the breizh café - Larcher, Betrand (London, United Kingdom : Jacqui Small LLP, 2015)
Creating enhanced traditional recipes that become exceptional dishes is what Breizh Cafe stands for - the perfect balance between simplicity and excellence.
Introduction -- The Regional Produce of Brittany -- How to make the perfect galette -- Galette batter -- Crepe Batter -- Appetizers -- Buckwheat galettes -- Dessert crepes -- Appendices.
Includes index.
Keywords: PANCAKES, WAFFLES, ETC